Meteorological Aspects of Gamma‐Ray Glows in Winter Thunderstorms. Issue 7 (9th April 2021) - Wada, Y.; Enoto, T.; Kubo, M.; Nakazawa, K.; Shinoda, T.; Yonetoku, D.; Sawano, T.; Yuasa, T.; Ushio, T.; Sato, Y.; Diniz, G. S.; Tsuchiya, H.
Abstract: During three winter seasons from November 2016 to March 2019, 11 gamma‐ray glows were detected at a single observation site of our ground‐based gamma‐ray monitoring network in Kanazawa, Japan. These events are analyzed with observations of an X‐band radar network, a ceilometer, a disdrometer, and a weather monitor. All the detected glows were connected to convective high‐reflectivity regions of more than 35 dBZ, developed up to an altitude of >2 km. They were also accompanied by heavy precipitation of graupels. Therefore, graupels in the lower layer of thunderclouds that correspond to high‐reflectivity regions can form strong electric fields producing gamma‐ray glows. Also, these events are compared with a limited sample of nondetection cases, but no significant differences in meteorological conditions were found between detection and nondetection cases in the present study. Plain Language Summary: Strong electric fields inside thunderclouds can accelerate electrons to relativistic energies, and gamma‐ray photons from the accelerated electrons can be observed as minute‐lasting "gamma‐ray glows." During winter thunderstorms in Japan, we detected eleven gamma‐ray glows at sea level. The observations were combined with meteorological measurements such as atmospheric temperature, cloud bases, types of precipitation particles, and radar‐echo measurements. All the detected gamma‐ray glows were taking place during a passage of tall and well‐developed radar‐echo regions, and accompanied by heavy precipitation of graupel/hail pellets. The graupel/hail particles in the lower layer of thunderclouds could have contributed to gamma‐ray glows production. Key Points: Eleven gamma‐ray glows were observed during three winter seasons at a single observation site in Japan All the detected gamma‐ray glows were associated with tall and well‐developed radar‐echo structures of thunderstorms Graupel pallets in the lower layer of thunderclouds could be related to downward electron acceleration for the gamma‐ray glows